Pemberdayaan Masyarakat Melalui Aplikasi Teknologi Inseminasi Buatan, Pengolahan Pakan , Biofarmaka dan Limbah dalam Upaya Pengembangan Sentra Kambing - Lilik Maslachah; Tri Wahyu Suprayogi; Widya Paramita Lokapirnasari (Direktorat Pengabdian kepada Masyarakat Universitas Gadjah Mada, 2019)
ABSTRACT Community empowerment of the goat farming group in Kerek and Merakurak, Tuban aims to improve the knowledge of artificial insemination technology of goats, processing agricultural and plantation waste products for goat feed,processing and using medicinal plants and processing goat’s faeces waste to become environmentally-friendly fertilizer. Methods: observing the location, interviewing and discussing with the leader of the group to clarify the problems faced by goat farmers. Education given by seminar and training by demos of artificial insemination, complete feed processing, bio-pharmaceutical preparation and waste processing. Evaluation and monitoring the success of the sustainability program cooperating with local animal husbandry department for assistance by field operators serving on the area. The output of TTG is transformation of artificial insemination technology of goats. Knowledge and understanding of farmers about how to process complete feed for goats. Making bio pharmaceutical preparation independently. Production of environmentally-friendly fertilizer. Keywords: artificial insemination; bio-pharmaceutical; complete feed; waste product